2009
DOI: 10.1258/td.2008.080124
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease: a clinical and epidemiological study of 70 children in Brazil

Abstract: This is a prospective study of a cohort of 70 children with Kawasaki disease (KD) admitted from April 2002 to April 2007 to a tertiary hospital in Brasilia, Brazil. Of the 70 children, only 32 (45.7%) were referred during the acute phase of the disease and only 15 (21.4%) were referred with the correct diagnosis. Coronary aneurysms were detected in 13 (18.5%). A high suspicion index is essential in order to detect new cases as KD is probably underdiagnosed in Brazil and other developing countries, and an early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In Brazil, a delayed diagnosis of KD by the primary physician is frequent even in age groups where KD is more prevalent. As found in a previous study from our laboratory, the most frequent misdiagnoses of KD were allergic reactions and exanthematous infectious diseases of infancy [11].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…In Brazil, a delayed diagnosis of KD by the primary physician is frequent even in age groups where KD is more prevalent. As found in a previous study from our laboratory, the most frequent misdiagnoses of KD were allergic reactions and exanthematous infectious diseases of infancy [11].…”
Section: Introductionsupporting
confidence: 78%
“…Coronary aneurysms appear in 15% to 25% of cases [7], often silent, and may be recognized only years later in the event of sudden death or myocardial infarction [4,7]. There are many infectious diseases more prevalent than KD that present as acute febrile illnesses of childhood, confounding the diagnosis of KD [11,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This often results in a wrong, delayed, or missed diagnosis. Studies from other resource-limited countries, such as Brazil, showed that only 46% of children with KD were referred and treated promptly within the rst ten days of onset of symptoms, and only 21% of them were referred with the correct diagnosis [10] . Among that cohort CAAs developed in 18.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of KD in Chile and Latin America report single-center experiences [12][13][14][15]. However, to our knowledge, population-based epidemiological studies of KD in Latin American countries have not been conducted.…”
Section: Introductionmentioning
confidence: 99%